2002
DOI: 10.1002/hed.10169
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of telomerase activation and telomere length in head and neck cancer

Abstract: Our results demonstrate the significant clinical usefulness of telomerase activation and telomere length for head and neck cancer patients. These markers may be helpful in predicting the clinical course of the disease and thus in identifying the patients in need of a close follow-up and vigorous adjuvant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
62
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 29 publications
6
62
0
Order By: Relevance
“…24 Patel et al studied telomere alterations by Southern blot analysis in tumor and adjacent normal tissues in 110 patients with head and neck cancer and 40 patients with precancerous and benign conditions. 20 Telomere lengths in this sample set were significantly lower in malignant tissues compared with the tumor adjacent normal tissues. In addition, while no significant correlation was observed between telomerase activation and clinicopathologic characteristics of the patients, 2-year disease-free survival analysis showed that patients with longer telomeres in malignant tissues had poor disease-free survival.…”
Section: Other Types Of Cancermentioning
confidence: 72%
See 4 more Smart Citations
“…24 Patel et al studied telomere alterations by Southern blot analysis in tumor and adjacent normal tissues in 110 patients with head and neck cancer and 40 patients with precancerous and benign conditions. 20 Telomere lengths in this sample set were significantly lower in malignant tissues compared with the tumor adjacent normal tissues. In addition, while no significant correlation was observed between telomerase activation and clinicopathologic characteristics of the patients, 2-year disease-free survival analysis showed that patients with longer telomeres in malignant tissues had poor disease-free survival.…”
Section: Other Types Of Cancermentioning
confidence: 72%
“…Studies indicating the prognostic potential of telomeres have also been reported for head and neck cancer, 20 neuroblastomas 21 and glioblastomas. 24 Patel et al studied telomere alterations by Southern blot analysis in tumor and adjacent normal tissues in 110 patients with head and neck cancer and 40 patients with precancerous and benign conditions.…”
Section: Other Types Of Cancermentioning
confidence: 92%
See 3 more Smart Citations